PAIN ASSOCIATED WITH LIVER BIOPSIES THROUGH PERCUTANEOUS APPROACH UNDER SONO-GRAPHIC GUIDANCE-A CROSS SECTIONAL PILOT STUDY IN A TERTIARY CARE HOSPITAL - Baig, Muhammad Akbar; Javed, Wajiha (Journal of Ayub Medical College Abbottabad, 2015)
Background: Pain is one of the most common and feared complication of percutaneous liver biopsy under local anaesthesia using sonographic guidance. This observational study was set to judge the intensity of pain felt by adult patients presenting for percutaneous liver biopsy with known/suspected underlying hepatic pathology. Methods: This observational cross sectional study which was piloted on 10% of the original sample size was conducted at Aga Khan University Hospital, Karachi. Study population was the adult patients coming for percutaneous liver biopsy at the Department of Radiology. Descriptive statistics were run, data was checked for normality. Means and Standard deviations were done for continuous variables and where data was skewed, median with inter quartile range was computed. Later data was clumped in categories, frequency and percentages were reported for categorical variables. Graphical representation of data was done. Results: A total of 50 patients were recruited. Minimum pain reported on visual analogue scale (VAS) was 0 and maximum as 4. 30% of patients rated 3 and similarly 30% of the people rated 4 on the VAS. Mean pain experienced was 2.7±1.11 and a median of 3 on VAS. This indicates that a minority of patients in our survey had a complaint of mild pain during the procedure. Conclusions: Percutaneous liver biopsy is a very safe procedure and minimal pain was felt by a minority of patients whereas the rest showed satisfaction from the procedure with no post procedural complaints. Keywords: Pain, Visual Analogue scale, percutaneous liver biopsy